Open Science at the University of Toronto: An Exploration of Researcher, Administrator, and Librarian Perspectives - Burt-D’Agnillo, Madelin; Thuna, Mindy (Partnership, 2024)
Objective: The impetus for this project is to understand open science practices and obstacles at the University of Toronto. This project uses open-ended questions to evaluate the ways in which university-affiliated individuals learn about, think about, and interact with open science. The goal of this study is to showcase the complexity and diversity of activity and challenges in this domain to help determine how best to move open science forward.Methods: From March to October 2022, 45 semi-structured interviews were conducted with faculty, graduate students, librarians, and administrators who were already engaging with open science in some form. Interviews were conducted and recorded using Zoom and the audio was transcribed using Otter.ai. As part of a commitment to open science practices, a data management plan was created and, with participants’ consent, 26 transcripts were uploaded to Dataverse. Data analysis used structured coding and thematic development to investigate responses.Results: There is no singular manifestation of open science at University of Toronto. The qualitative findings reflect a diversity of opinions, practices, and relationships to open science. Results are limited to individuals who have knowledge and experience with open science and are not representative of the broader research landscape at the university.Conclusion: For open science to have longevity, there must be systemic changes to adopt more open practices. The University of Toronto is well positioned to guide the transition and harness open principles to move into the future.